Sensitivitas ekstrak tanaman kemangi (Ocimum sactum) terhadap bakteri Aeromonas hydrophila - Sambuaga, Mutiara E.; Longdong, Sammy N.J.; Manoppo, Henky (e-Journal BUDIDAYA PERAIRAN, 2018)
The research was conducted to appraise the antimicrobial activity of Ocimum sactum extract on A. hydrophila. Fresh basil was purchased from the local market,  put in plastic bags and brought to Laboratory of Fish Health, Environment, and Toxicology, Faculty of Fisheries and Marine Science Sam Ratulangi University.  The basil was cleaned and separated between trunk and leaf, and then macerated in alcohol 70% at room temperature for 24 hours. The extract was filtered using Whatman paper and evaporated using rotary evaporator. Paper disc (diameter: 6 mm) was immersed in the extract,  placed on TSA previously inoculated with A. hydrophila, and incubated at 28oC for 24 hours.  The result showed  that trunk and leaf extracted with alcohol 70% did not inhibit the grow of bacteria while aquades extract was able to inhibit growth of bacteria indicated by the present of clear zone around the paper discs with a diameter of 16.5 mm for leaf and 20.5 mm for basil trunk. The ability of these two extracts to inhibit the growth of bacteria was categorized as strong. Thus, aquades extract of basil was able to inhibit the growth of pathogenic bacteria. Keywords: Ocimum sactum, antimicrobial, disc diffusion method, medicinal plant,  inhibition zone